Features of evaluation during distance learning - Nalyvaiko , O.; Kutsyna , K. (Scientific notes of the pedagogical department, 2021)
In the context of the COVID-19 pandemic, distance learning has become the main way to get an education. This gave impetus to the development and involvement of innovative information technologies in the management of the educational process. It, like other forms, has both advantages and disadvantages. One of the main components of the educational process is the verification and evaluation of educational achievements, which should be carried out at a distance. Control over the assimilation of material in this way of acquiring knowledge has its difficulties. Analysis of the literature of foreign sources only confirms that the topic of distance learning assessment is becoming increasingly important and needs to be developed and improved. The article considers the problem of knowledge assessment during distance learning and searches for the optimal model of control and ways to increase the effectiveness of control of educational achievements with the involvement of new forms and innovative technologies. Obviously, assessment during distance learning requires systematization and standardization and has prospects for further development in the field of control of knowledge acquisition. This direction of distance education development is a priority today and requires close attention of modern pedagogy.